Top-hat crashboxes of thermoplastic fibre-metal-laminates processed in one-step thermoforming: Experimental and numerical study. (1st December 2021) - Harhash, Mohamed; Fischer, Tobias; Grubenmann, Michael; Hua, Wei; Heingärtner, Jörg; Kuhtz, Moritz; Gude, Maik; Hora, Pavel; Ziegmann, Gerhard; Palkowski, Heinz
Abstract: Recently, the applicability of thermoplastic fibre-metal-laminates (FMLs) in the automotive and aerospace fields has gained more attention due to their lightweight potential and improved flexural stiffness. Therefore, this study deals with investigating the structural properties of FMLs top-hat crashboxes under quasi-static and highly-dynamic bending conditions. Accordingly, the energy absorption characteristics and failure modes including the arisen microscopic defects are identified. For improved structural integrity, the hat structures were produced using a one-step thermoforming process, in which the forming and bonding of the FMLs layers take place simultaneously. Different metallic skin sheets (aluminium and steel) combined with glass fibre reinforced polyamide cores with different fibre orientations and thicknesses were considered. Also, finite element analysis using LS-Dyna™ was carried out on the Al-based FMLs to calculate the energy absorption behaviour and analyse the failure modes. To characterize the monomaterials and FMLs, tensile tests at different temperatures and strain rates were performed. The results state that with the thermoforming process, arbitrary FMLs material combinations and thicknesses can be processed. Varied thicknesses in the different hat structure regions are expected due to the flow of the polyamide matrix. Moreover, increasing the core thickness and utilizing the 0°/90° fibre orientation can improve the bending stiffness. Several defects such as delamination, plastic deformation and fibre cracking arose during the bending test. Finally, the simulation results revealed good agreement with the experimental ones. Due to the model simplifications, some failure modes could not be replicated in the simulation. This requires further studies.